Scaleup Condensation Process in Preparation of Flumorph - Sun, Dequn; Hu, Changyan; Yang, Yue (Asian Journal of Chemistry, 2014)
The flumorph is a patented pesticide developed in China. This work reported the scalup preparation in which the sodamide was employed as an effective base for the condensation between diketone and acetyl morphilin. The assay and yield of the flumorph were reached over 95 % and 80 %, respectively. This process is very competitive compared with other related methods due to lower cost and environment friendly advantages.